Model Pembelajaran Tutor Sebaya Pada Materi Sistem Peredaran Darah Manusia - SITUMORANG, GOLDA NORA; RUMAHORBO, BASA T. (Jurnal Ilmu Pendidikan Indonesia, 2019)
This study aims to determine the differences in models of peer tutors on learning outcomes in the material of the Human Circulatory System. The method used in this study was experimental guasi with a sample of 100 people divided into two classes namely the control and experiment classes. The results of the study revealed that there were differences in learning outcomes between classes using the model of peer learning with conventional learning models this was evidenced by the value of Asymp. a large (2-tailed) value of 0,000 is generated from the T-test and the n-Gain average value uses peer tutors of 0.73 and a high category and those using the conventional learning model 0.34, the medium category